OVERCROWDING DI LEMBAGA PEMASYARAKATAN - Edi Suranta; Cemby Agustina; Irene Anastasya Sinaga; Vita Daniela B.V.R Oematan (Pusat Kajian Lembaga Pemasyarakatan, Fakultas Hukum, Universitas Kristen Indonesia, 2026)
Correctional institutions are a vital part of the correctional system, serving to foster inmates so they can be reintegrated into society. However, as the number of inmates increases, many prisons are experiencing overcrowding because the number of inmates is not proportional to the available capacity. This study aims to directly describe effective solutions to address the problem of overcrowding in Indonesian correctional institutions and identify policies that have been implemented to address this issue. The method used is empirical juridical research, focusing on legal aspects and facts on the ground, as well as a socio-legal approach to analyze issues related to social injustice. The data used are secondary data collected through literature studies, including primary and secondary legal materials. The results of the study indicate that various factors influence overcrowding, and current policies have not yet had a significant impact on reducing overcrowding in prisons.